Graphene Grown on Ni Foam: Molecular Sensing, Graphene-Enhanced Raman Scattering, and Galvanic Exchange for Surface-Enhanced Raman Scattering Applications - Messina, María Mercedes (2018)
The growing of graphene on irregular 3D Ni structure demonstrates to be aninteresting platform for, molecular sensing, GERS, and SERS applications after galvanicexchange of Ag + ions. Raman, SEM (EDS), optical images, and diffuse reflectance exhibitthat graphene grows in multilayer (MLG) fashion with different stacking configurations.Statistics performed employing Raman show that as-grown graphene can be classified intwo main stacking configurations: AB (or Bernal stacking) and rotated graphene which areseparated by a 2D full-width half maximum (fwhm) threshold of ~30 cm -1 . Rotatedstacking senses low concentrations of methylene blue (MB) at 10 -6 M concentration,whereas AB-stacking seems to be much less sensitive upon molecular adsorption. Galvanicexchange of Ag leads to agglomerates preferentially formed on top graphene wrinkleswhich ultimately became target-spots for performing SERS. Our experiments demonstratethat as-grown graphene, comprised of different stacking configurations, can be used as amolecular sensor and detect nanomolar concentrations of MB and thiram (by SERSapplications), after galvanic exchange with Ag.